The Peduli Lindungi Administration Services On Swab Patient: A Cash On Clinic dr. H. Abdul Rofieq Depok - Audina, Soraya; Amirul, Amirul (International Publisher (YAPENBI), 2022)
In the early of 2020 Indonesia was faced on victim of Crorona virus 19 (Covid-19). This syndroms was known as the pharyngal capacity in which the patient fell it is hard to breath, hight temperature, lost of power and it ends with the dead. Most of the countries over the world experience this syndroms. As for Indonesian goverment, this problems is seen as the most serious problem and goverment exposed some regulations such as social distancing,away from the crowded, weqr mask and the compulsary of vaccimes of all indonesian people. The swab Antigen program is employed to people to detect whether someone is suspected or unsuspected to Covid 19. The process of swab Antigen is carried out by Nosafaring system in which the nose muccus by using the cotton bud and finnaly the muccus is tested in labratoriun to get information corona virus syndroms on patient. The most serious problem for society to go to health centre for Swab Antigen is the procedure of administration which seem complicated and society seem rhe victim of Covid 19 as the common diasase. They would rather stay home than go to medical centre for checking their health. The investigation was held in Clinik dr. H. Abdul Rofieq. Depok to see how it s service make everything easy for patient to have the medical health. The investigation is qualitative one in which some questions are adressed to the caretaker of clinic to see the effectiveness of service in administration and the motivation of patient to go to medical centre for swab antigen. The finding sows thats more and more patients go to Clinic dr. H Abdul Rofieq for health.